Low-cost and facile implementation of microfluidic colour-changing devices using dry film photoresist-based moulds. Issue 1 (1st January 2018) - Zhang, Min; Li, Songjing
Abstract: In this work, different microfluidic colour-changing devices are implemented by using dry film photoresist-based moulds instead of standard photolithography moulds. EtertecHT-115T negative dry film photoresist is employed to realise the rapid fabrication of the moulds for colour-changing layers. The major factors that may affect the fidelity of the dry film moulds during fabrication are summarised and analysed, including the optimum exposure times and the appropriate developing times. Especially, the impacts of different concentrations of sodium carbonate (Na2 CO3 ) solution on developing rate are investigated for 1–5 layers (50–250 μm thick) of EtertecHT-115T dry film photoresists by experiments. The created dry film moulds show the advantages of low cost, high manufacturing efficiency and requiring no professional training. Each application of the microfluidic colour-changing devices presents high transparency and good colour-changing effect. The microfluidic colour-changing layers based on dry film moulds can be used in different wearable devices of human, and also can be applied for realising surface camouflage and display functions of soft machines/robotics.